Beispiel Nr: 05
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 1 x +2 + 3 z=4\\ 2 x +3 y + 2 z=6\\ 0 x +2 y + 6 z=0\\ \\ \\ \textbf{Rechnung:} \\ 1 x + 2 y + 3 z=4\\ 2 x +3 y +2 z=6\\ 0 x +2 y +6 z=0\\ D_h=\left|\begin{array}{ccc} 1\ & 2 & 3\\ 2&3 & 2\\ 0& 2 & 6 \\ \end{array}\right| \begin{array}{cc} 1\ & 2 \\ 2&3 \\ 0& 2 \end{array} \\ D_h=1 \cdot 3 \cdot 6+2 \cdot 2 \cdot 0 +3 \cdot 2 \cdot 2 - 3 \cdot 3 \cdot 0 -1 \cdot 2 \cdot 2 -2 \cdot 2 \cdot 6=2 \\ D_x=\left|\begin{array}{ccc} 4\ & 2 & 3\\ 6&3 & 2\\ 0& 2 & 6 \\ \end{array}\right| \begin{array}{cc} 4\ & 2 \\ 6&3 \\ 0& 2 \end{array} \\ D_x=4 \cdot 3 \cdot 6+ 2 \cdot 2 \cdot 0 +3 \cdot 6 \cdot 2 - 3 \cdot 3 \cdot 0 - 4 \cdot 2 \cdot 2 -2 \cdot 6 \cdot 6=20\\ D_y=\left|\begin{array}{ccc} 1\ & 4 & 3\\ 2&6 & 2\\ 0& 0 & 6 \\ \end{array}\right| \begin{array}{cc} 1\ & 4 \\ 2&6 \\ 0& 0 \end{array} \\ D_y=1 \cdot 6 \cdot 6+4 \cdot 2 \cdot 0 +3 \cdot 2 \cdot 0 - 3 \cdot 6 \cdot 0 -1 \cdot 2 \cdot 0 -4 \cdot 2 \cdot 6=-12 \\ D_z=\left|\begin{array}{ccc} 1\ & 2 & 4\\ 2&3 & 6\\ 0& 2 & 0 \\ \end{array}\right| \begin{array}{cc} 1\ & 2 \\ 2&3 \\ 0& 2 \end{array} \\ D_z=1 \cdot 3 \cdot 0+2 \cdot 6 \cdot 0 +4 \cdot 2 \cdot 2 - 4 \cdot 3 \cdot 0 -1 \cdot 6 \cdot 2 -2 \cdot 2 \cdot 0=4\\ x=\frac{20}{2} \\ x=10 \\ y=\frac{-12}{2} \\ y=-6 \\ z=\frac{4}{2} \\ z=2\\ L=\{10/-6/2\} $